Experimental demonstration of coupled optical springs. (12th January 2017) - Gordon, N A; Barr, B W; Bell, A; Graef, C; Hild, S; Huttner, S H; Leavey, S S; Macarthur, J; Sorazu, B; Wright, J; Strain, K A
Abstract: Optical rigidity will play an important role in improving the sensitivity of future generations of gravitational wave (GW) interferometers, which employ high laser power in order to reach and exceed the standard quantum limit. Several experiments have demonstrated the combined effect of two optical springs on a single system for very low-weight mirror masses or membranes. In this paper we investigate the complex interactions between multiple optical springs and the surrounding apparatus in a system of comparable dynamics to a large-scale GW detector. Using three 100 g mirrors to form a coupled cavity system capable of sustaining two or more optical springs, we demonstrate a number of different regimes of opto-mechanical rigidity and measurement techniques. Our measurements reveal couplings between each optical spring and the control loops that can affect both the achievable increase in sensitivity and the stability of the system. Hence this work establishes a better understanding of the realisation of these techniques and paves the way to their application in future GW observatories, such as upgrades to Advanced LIGO.